Challenges to Rural NEETs’ Transition From School to Work in Lithuania During the COVID-19 Pandemic - Vyšniauskienė, Sonata; Brazienė, Rūta (Calitatea Vieții, 2023)
This paper discusses challenges to rural NEETs' transition from school to work in Lithuania during the COVID-19 pandemic. The focus is on identifying the main issues related to the successful transition of young people from education to the labour market. The paper draws on extensive research on NEET youth transition from school to work in Lithuania, using mixed research methods including social and public policy, survey research on NEETs registered with the PES and a secondary data analysis (Eurostat data on NEETs). The study is based on survey research conducted in Lithuania from February to April 2021. A total of 453 young people who were unemployed and registered with the PES participated in the study. A subjective evaluation of the attitudes and experiences in the Lithuanian labour market of the unemployed youth (aged 18 to 35 years), registered with the PES and living in rural areas is presented. The results reveal that more young people living in rural areas claim that their situation in the labour market worsened considerably during the pandemic. Despite the fact that a number of active labour market policies targeting the NEET group are in place, specific policy measures targeting young NEETs living in rural areas need to be developed in order to address their specific needs.